Identificación de la proteína responsable del sinergismo del complejo viral de camote (SPVD) - Cruzado, R.K. (2010)
Viruses diseases are one of the limiting factors of sweetpotato (Ipomoea batatas (L) Lam) production. The most severe disease is caused by Sweet potato virus disease (SPVD). It is caused by the synergistic interaction between Sweet potato feathery mottle virus (SPFMV, Potyviridae) and Sweet potato chlorotic stunt virus (SPCSV, Closteroviridae). Many sweetpotato cultivars are highly resistant to infection by SPFMV alone, which is presumed to be due to a gene silencing- based defense system. Previous research found that SPCSV encodes proteins that can suppress gene silencing which could be responsible for viral synergism in SPVD. The aim of the present study was the identification of the viral protein(s) responsible for this synergistic interaction. We generated sweetpotato transgenic plants expressing the SPCSV proteins p22 and RNase3, and they were tested by infection with SPFMV. The results suggest that RNase3 is the protein responsible for viral synergism in SPVD. We found that disease symptoms and SPFMV titers in RNase3-transgenic plants were similar to those produced in non-transgenic plants infected with SPVD. The identification of this viral protein is important to obtain SPVD resistant plants by genetic engineering.